Alx1 Deficient Mice Recapitulate Craniofacial Phenotype and Reveal Developmental Basis of ALX1-Related Frontonasal Dysplasia - Iyyanar, Paul P. R.; Wu, Zhaoming; Lan, Yu; Hu, Yueh-Chiang; Jiang, Rulang (Frontiers in Cell and Developmental Biology, 2022)
Loss of ALX1 function causes the frontonasal dysplasia syndrome FND3, characterized by severe facial clefting and microphthalmia. Whereas the laboratory mouse has been the preeminent animal model for studying developmental mechanisms of human craniofacial birth defects, the roles of ALX1 in mouse frontonasal development have not been well characterized because the only previously reported Alx1 mutant mouse line exhibited acrania due to a genetic background-dependent failure of cranial neural tube closure. Using CRISPR/Cas9-mediated genome editing, we have generated an Alx1-deletion mouse model that recapitulates the FND craniofacial malformations, including median orofacial clefting and disruption of development of the eyes and alae nasi. In situ hybridization analysis showed that Alx1 is strongly expressed in frontonasal neural crest cells that give rise to periocular and frontonasal mesenchyme. Alx1del/del embryos exhibited increased apoptosis of periocular mesenchyme and decreased expression of ocular developmental regulators Pitx2 and Lmxb1 in the periocular mesenchyme, followed by defective optic stalk morphogenesis. Moreover, Alx1del/del embryos exhibited disruption of frontonasal mesenchyme identity, with loss of expression of Pax7 and concomitant ectopic expression of the jaw mesenchyme regulators Lhx6 and Lhx8 in the developing lateral nasal processes. The function of ALX1 in patterning the frontonasal mesenchyme is partly complemented by ALX4, a paralogous ALX family transcription factor whose loss-of-function causes a milder and distinctive FND. Together, these data uncover previously unknown roles of ALX1 in periocular mesenchyme development and frontonasal mesenchyme patterning, providing novel insights into the pathogenic mechanisms of ALX1-related FND.